Variáveis fisiológicas e estresse oxidativo de eqüinos durante campeonato de enduro - Teixeira Neto, Antônio Raphael [UNESP] (2006)
The aim of this study was to register the physiologic and metabolic alterations and investigate the exercise induced oxidative stress that Arabians horses undergo during long distance endurance exercises, under tropical climate. Five endurance rides were followed through 2004 state championship. Blood samples were collected from jugular vein 2 to 5 hours before the beginning of each ride and during rides, after the veterinary check-point. During the recovery period, venous samples were collected 24, 48 and 72 hours after the rides, at each horses stables. Hemoconcentration (elevated erythrocytes count, hemoglobin concentration and hematocrit), dehydration (elevated total plasmatic proteins concentration and weight losses) and, possibly, decreased renal perfusion (elevated seric urea and creatinin concentration) were revealed by horses in this study. All data returned to basal values during the recovery period except serum urea concentration. Hormonal changes were also monitored and data revealed an important elevation in plasma cortisol concentration during the ride, directly related to the duration of it. Insulin response was decreased by catecholamines suppressing action during exercise. The endurance effort, evaluated in this experiment, could induce muscular alterations by an increase in muscular enzyme activities during the rides, with different periods of return to basal values in the recovery period. An interesting result was the exercise-induced oxidative stress measured by cyclic voltammetry to determine the total antioxidant capacity of plasma during endurance exercise. The results of this study can contribute to a better understanding of what really occurs in the horses body to maintain homeostasis while submitted to long distance endurance efforts under tropical climate.